Peach Root-knot Nematode - Mary Ann D. Maquilan; Ali Sarkhosh; Donald W. Dickson (EDIS, 2018)
One of the production issues that peach growers in Florida must contend with is plant-parasitic nematodes. One such species is the more recently discovered peach root-knot nematode, Meloidogyne floridensis, which is the subject of this 5-page publication. Written by Mary Ann D. Maquilan, Ali Sarkhosh, and Donald Dickson and published by the UF/IFAS Horticultural Sciences Department, July 2018. http://edis.ifas.ufl.edu/hs1320